Detección hematológica de Anaplasma phagocytophilum en caballos de la provincia de Chiclayo, Perú - Masgo C., Deysi (2020)
The aim of this study was to detect Anaplasma phagocytophilum in horses from the province of Chiclayo, Peru, using haematological techniques. One hundred blood samples were collected from apparently healthy horses with a history of exposure to ticks. The haematological study consisted of blood count and the evaluation of blood smears stained with Wright and acridine orange to search for inclusion bodies and morulae of the pathogen. Results showed that 9% of horses (9/100) presented structures compatible with inclusion bodies or morulae of A. phagocytophilum, so they were considered as "positive". This group of animals presented slight alterations in the leukocytic and thrombocytic series. The findings indicate the presence of A. phagocytophilum in horses in Peru.